Designing a Design System - Lilja, Malin; Lundkvist, Fredrika (My University, 2019)
ABSTRACT A great way of saving both time and money is making sure work is not repeated. Today, many companies have started to create design systems to enable for more efficient digital product development, while also aid communication between the people involved. At the region of Västra Götaland in Sweden there has been a start to creating a design system, called “komponentkartan” or “the component map” translated into English. However, the design system has been created in a way that has left it inconsistent, and instead of helping the designers and developers with communicating it has created some dual meanings and double interpretations of things. The purpose of this master thesis was to understand what a design system is and research best practices to design and improve a new design system for the region of Västra Götaland’s IT department. The design system would primarily be used for the IT department’s development of remuneration systems. The work included benchmarking and case studies to understand design systems from an outside as well as an inside perspective, complementing the literature review. The work had also a heavy emphasis on the users of the design system and their needs. Through iterations with user research the design system’s requirements were defined and were used as a basis for the concepts. The concepts were iterated in three steps with users and went from low fidelity to high fidelity prototypes. The result was not just a design system website, but also a process of working so that the users could make the design system stay relevant for their products. The final design system included a on boarding process for new users as well as showing the benefits of the system in a clear way to those not actively using the system, but has more control over it, such as the organisation. It has guidelines to help a developer of the design system to make coherent content, creating recognition and better understanding for an experienced user of where to find information and how. The final design system aids a user to edit and contribute, using the help of GitHub as a base. In these ways, the final design creates a better user experience, and the process of a design system can be better established and worked with at the region of Västra Götaland’s IT department.
Keywords: design system, style guide, pattern library, components, user-centred design, UX; user interface, UI